2013
DOI: 10.1371/journal.pone.0056861
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylesterase 1 Gene Duplication and mRNA Expression in Adipose Tissue Are Linked to Obesity and Metabolic Function

Abstract: Context and AimsCarboxylesterase 1 (CES1) appears to play an important role in the control of the metabolism of triglycerides and cholesterol in adipocytes and other cell types including hepatocytes. Therefore, it is relevant to gain insights into the genetic versus non-genetic mechanisms involved in the control of CES1 mRNA expression. Here, we investigated CES1 mRNA expression level in adipose tissue and its association with measures of adiposity and metabolic function in a population of elderly twins. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…In recent years, the morbidity of metabolic diseases has continued to grow, and hyperlipidemia is one common type of metabolic disease. To date, only a handful of studies have been conducted regarding the relationship between metabolic syndrome and CES, and these have mainly focused on the CES-mediated hydrolysis of the endogenous lipids [35][36][37]. Even so, there are some reports about the influence of a HFD on the hydrolysis of drugs that contain ester bonds and that are catalyzed by CES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the morbidity of metabolic diseases has continued to grow, and hyperlipidemia is one common type of metabolic disease. To date, only a handful of studies have been conducted regarding the relationship between metabolic syndrome and CES, and these have mainly focused on the CES-mediated hydrolysis of the endogenous lipids [35][36][37]. Even so, there are some reports about the influence of a HFD on the hydrolysis of drugs that contain ester bonds and that are catalyzed by CES.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an HFD did not alter most mRNA expression levels of most lipase/ esterases in the adipose tissue [35]. Importantly, the CES1 mRNA expression levels in the adipose tissues were positively associated with the body-mass index and the TG levels [36]. An HFD appeared to induce a slight upregulation of CES in the plasma [37].…”
Section: Introductionmentioning
confidence: 88%
“…It is involved in xenobiotic (Redinbo et al, 2003), fatty acid and cholesterol (Jernås et al, 2009) metabolisms. Mutations within the 16q12.2 cytoband or the CES1 gene have been connected with cerebral cortical malformations (Piao et al, 2002), amyotrophic lateral sclerosis (Abalkhail et al, 2003), anti-tuberculosis drug-induced hepatotoxicity (Wu et al, 2012) and obesity (Friedrichsen et al, 2013). Even though we do not know the correspondent pathway, the association of this CNVR with AD is promising given the fact that the spanned genes have a direct relationship with liver and hydrolysis functions involving the alcohol compound.…”
Section: Discussionmentioning
confidence: 99%
“…CES1 hydrolyzes the aforementioned substrates by releasing an alcohol substituent to form a fatty acylenzyme intermediate that reacts with water and releases an acyl groupcontaining molecule. CES1 is involved in the deesterification and transesterification of lipids as it has cholesterol transferase activity, which enables the formation of cholesteryl esters in the pres ence of free cholesterol [22]. It has also been reported that regulation of macrophage reverse cholesterol transport (mRCT) is facilitated by hydrolytic CES metabolism of chol esteryl esters found within cytoplasmic lipid droplets [23].…”
Section: Function Isoenzymes and Structure Of Carboxylesterasesmentioning
confidence: 99%
“…CES1A3 results from gene duplication and has been shown to increase the production of CES1 and, hence, CES1 activity [22]. It has been reported that the "daughter" copy of the gene is transcribed at a lower level than the "mother" copy and the transcripts of CES1A3, and its func tional counterpart can compete for the same transacting factors involved in mRNA degradation [22]. Thus, the high levels of transcripts generated from CES1A3 may protect the transcript of the functional homolog from degradation and thereby increase its translation.…”
Section: The Genetics Of Ces1 and Ces2mentioning
confidence: 99%